Strangers and Enemies or Partners? Hebrew Translations of Palestinian Literature - Writers, Contents and Texts: حول الترجمة من الادب الفلسطيني الى العبرية - مؤلفون, مضامينوفصوص - Amit-Kochavi, Hannah (Jama’a: an Interdisciplinary Journal of Middle East Studies, 2003)
The article studies Hebrew translations of Arabic literary works by Palestinian writers such as Khalil al-Sakakini, Rashid Hussein, Fadwah Tuqan, Sahar Khalifah, and Mahmoud Darwish, who live in the West Bank, the Gazza Strip, and the Palestinian diaspora. It discusses the inter-relations between the political background (the Israeli-Arab conflict) and the Hebrew translation and publication of this literature. It further examines the gradual change in the status of the translations vis-a-vis the Israeli Hebrew target culture.